Análise dos fatores associados à cessação do tabagismo em Cuiabá/MT, 2014 - Pawlina, Maritza Muzzi Cardozo (2014)
Smoking is a disease and is considered a public health problem and also a risk factor for other diseases that cause a great impact on morbidity and the mortality of the population. It is indispensable to seek ways to mitigate this reality and tackle this complex disease, offering expert assistance to people who want to quit smoking and fail because of hindering factors that interfere with this process. This research has the general objective of analyzing the factors associated with smoking cessation in health facilities in Cuiabá, MT. To meet the objective of this study, four articles are presented, each one with an operational goal. In the first article, the association between sociodemographic characteristics, smoking status, degree of motivation, levels of anxiety, depression and stress in patients who have failed in a smoking cessation program are analyzed. A cross-sectional study was conducted on patients who sought smoking cessation programs in Cuiabá, MT, Brazil. All the smokers that were enrolled at the beginning of these programs, from May to August 2012, were invited to participate in this study, totaling 216 patients. The instruments used were the SocioDemographic Profile questionnaire, the Fagerström Test (FTND), Urica, the Beck Anxiety Inventory (BAI),the Beck Depression Inventory (BDI) and Lipp’s Stress Symptoms Inventory (LSSI). The data was entered twice in an electronic database, Epidata version 3.1, and a model of the Poisson regression was used for data analysis. Associations with treatment failure were found with the following variables: younger age group; less time spent smoking; larger consumption of cigarettes per day and lower degree of motivation. In the final model (RPa), the following were associated with variable weakness: less time spent smoking (RPa 1.53; 95% CI 1.07 to 2.32), greater smoking history (RPa 1.48; 95% CI 1.12 to 1.95), low level of motivation (RPa 1.58; 95% CI 1.07 to 2.32), and high level of anxiety (RPa 1.22; 95% CI 1.01 to 1.48). Low level of motivation (Contemplation and Pre-contemplation), high level of anxiety (moderate to severe), less time spent smoking, and a greater smoking history are associated with treatment failure. In the second article, the association of the dependency of nicotine with the level of anxiety and depression in patients in the smoking cessation program are analyzed. A cross-sectional study of patients in the smoking cessation programs in Cuiabá, MT was conducted. All the smokers enrolled, from May to August 2012, participated in this study. Four instruments were applied: the Socio-Demographic questionnaire, the Fagerström Test, the Beck Anxiety Inventory, and the Beck Depression Inventory. A bivariate analysis was done, the reason for the gross prevalence, with a significant level of 5% (p<0.05), having nicotine dependence as a variable ≥ a 5 (Fagerström). The associations with p <0.20 were selected for the multiple robust Poisson regression (RPa). Associations of Fagerström ≥ 5 with males were found; quantity of cigarettes smoked per day and level of depression, moderate or severe. In the final model (RPa), these associated variables continue: male (RPa 1.12; 95% CI 1.01 to 1.24), number of cigarettes per day (RPa 1.28; 95% CI 1.15 to 1.43) and a high level of depression (RPa 1.12; 95% CI 1.01 to 1.23). High nicotine dependence was significantly associated with the level of depression, showing the association between smoking and psychiatric comorbidity. In the third article, taking into consideration the non-adherence to treatment one of the hindering factors in the process of smoking cessation, the objective is to compare sociodemographic characteristics, smoking status and the degree of motivation among smokers who have or not left smoking treatment and analyze the association between sociodemographic factors and smoking. This was a cohort study of 216 smokers who sought treatment at health facilities in Cuiabá, MT. Sociodemographic and smoking questionnaires, degree of dependence (Fagerstrom), phase of motivation (Urica) and screening for alcoholism (Cage) were used. The initial evaluation data, after 45 days and 6 months of follow-up were charted and analyzed, considering the differences between abandonment and non abandonment and using the two proportions test 10 (α<0.05). A bivariate analysis was conducted, crude prevalence ratio, significance level of 5% (P < 0.05), having the variable outcome the abandonment of treatment. Associations with P < 0.20 were selected for multiple robust Poisson Regression (RPa).The dropout rate was 34.26%, with the highest rate of after the initial interview (17.59%). The calculation of the proportion of abandonment and non abandonment shows that the variables, males (p=0.030; Δ = 15.01), 20-39 age group (p=0.011; Δ = 16.17), (p=0.007F; Δ = 13.61), having a job (P=0.016; Δ = 15.93) and degree of motivation precontemplation and contemplation (p=0.008 and Δ = 12.31) was predominant in the dropout group. The lowest average time spent smoking (27.10, p=0.001) and lowest average tobacco intake (34.20, p=0.043) was also predominant in the treatment dropout group. Abandonment was associated with the male gender, 20-39 age group, employment, and motivation. In the final model, (RPa), gender (RPa 1.47; CI 95% 1.03-2.10) and age group (RPa 3.77; CI 95% 1.47-9.67) remained associated with abandonment. I concluded that male patients, aged 20-39, who have a job, a low motivational level (pre-contemplation and contemplation), lower average time spent smoking and lower tobacco intake dropped out more often from the treatment of nicotine dependence. In the fourth article, the objective was to compare the changes in the level of anxiety, depression, motivation and stress in patients in the smoking cessation programs in Cuiabá, MT. A cohort study was conducted in 3 phases: Phase A1 (initial assessment), A2 (45 days later) with medication and cognitive behavioral therapy, and A3 (6 months later). A sociodemographic questionnaire and smoking status, Urica, Cage, BAI, BDI and ISSL were used. Data was analyzed with nonparametric tests for paired comparisons in the three assessments carried out, Wilcoxon test. The results show a reduction in the levels of anxiety, depression, motivation (precontemplation and contemplation) and stress when comparing A1 with A2 and A1 with A3. The interventions conducted were effective in decreasing levels of anxiety, depression and stress, as well as increasing motivation.